A model for enhancing social media crisis communication for resilience building: a preliminary analysis - Mundottukandi, Mohammed S.; Jusoh, Yusmadi Yah; Haizan Nor, Rozi Nor; Che Pa, Noraini; Bukar, Umar Ali (Indonesian Society for Knowledge and Human Development, 2024)
What matters to people during a crisis is returning to their normal lives quickly and effectively. As a result, there has been a significant increase in interest in crisis recovery and resilience, particularly regarding the effects of crises and the role of social media in informing stakeholders. Prior studies assessing public resilience predictors and the impact of social media activities on resilience are lacking in identifying the factors that influence people's ability to recover from a crisis through social media crisis communication. Thus, the purpose of this study is to conduct a preliminary analysis to determine the impact of social media usage, information seeking, and information sharing on public resilience. A total of 107 items were developed based on the literature covering the following topics: Information Seeking (media choice, crisis type, uncertainty avoidance, framing, trust, efficacy, and perceived risk), Information Sharing (sentiment, richness, and authority), Social Media Usage (media exposure and uncertainty), and Resilience. Four experts validated these items using adjusted Kappa statistics and the content validity index. Subsequently, 30 responses were used in a pilot test to assess the reliability of the instruments, after 94 items passed expert validation. To evaluate the reliability of the items, Cronbach's alpha was employed. The results show that all the items were reliable, with Cronbach's alpha values ranging from 0.748 to 0.861. Therefore, the constructs satisfied the internal consistency requirement based on the obtained results. Overall, the study provides foundation for both theoretical advancements and practical applications in the domain of social media crisis communication.